Key-frame extraction for summarization of surveillance footage by analysis of colour histograms - Tyagi, Gauri; Kapur, Bhrigu; R, Sathyaraj (International Journal of Engineering and Technology, 2019)
Everyday a plethora of video content is generated by surveillance cameras all over the world. This footage has two major problems, it takes a lot of space even for parts that are not important (empty rooms, night time recording etc) and also takes a lot of time to review the same. Our objective through this paper is to reduce the spatial and temporal redundancies of the video through a process known as video summarisation. This paper proposes a summarization algorithm for surveillance footage via key-frame extraction, based on comparison of consecutive frames of the video over certain frame descriptors. The algorithm avoids exhaustive comparison by using K-means on the colour bins of each temporal shot to extract dominant colour bins to extract relevant sections of the surveillance footage. Experiments are performed on the i-Lids dataset for AVSS (Advanced Video and Signal based Surveillance) 2007 and EC Funded CAVIAR projectâ€™ dataset on city surveillance. Ground truth was used as the metric to judge the validity of the proposed algorithm. The obtained values from the algorithm are evaluated for precision, recall and F-measure. We found out that our algorithm satisfies the ground truth of the all video datasets and is also fast enough to perform the action. We conclude by showing the results and their comparisons of how our algorithm performs by highlighting various metrics of precision and accuracy.Â Â Â